Advancing library operations with AI: data-driven insights for academic resource management - Néstor A. Nova; Hernán Morales; Juan Pájaro; Andrea González (Information Research: An International Electronic Journal)
Introduction. The rapid evolution of artificial intelligence technologies affords opportunities and challenges for libraries. The study analyses the application of artificial intelligence tools for business intelligence purposes in a university library.